PELAYANAN ADMINISTRASI KARTU IDENTITAS ANAK (KIA) SECARA ONLINE DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG JAWA TENGAH - Rahmawati Sururama; Alfariz Firdausya Bintang Permana (Jurnal Media Birokrasi, 2021)
One product of population documents that is useful for ensuring the validity of child population data is the Child Identity Card (KIA). However, there are still many people who still doubt the benefits of the Child Identity Card (KIA), including the Child Identity Card (KIA) which is still considered less important by the residents because there are still many who do not know its use and application. The purpose of this study was to find out how the Online Child Identity Card (Kia) Issuance Service at the Department of Population and Civil Registration Semarang City, Central Java. In this study the author will use a descriptive qualitative method with an inductive approach. Data collection techniques using observation, documentation, interviews. Data analysis techniques using data reduction, data display/data presentation, conclusion drawing/verification. The results of this study, namely the online Child Identity Card (KIA) service carried out by the Semarang City Population and Civil Registration Service as a whole can be said to be good, but there are still obstacles that hinder the lack of staff in providing services. The Semarang City Population and Civil Registration Office opens vacancies and recruits daily freelancers who have good competence and ability so that they can provide optimal and maximum services to the community in the online Child Identity Card (KIA) Service process at the Semarang City Population and Civil Registration Service. Keywords: Service, Administration, Child Identity Card